2008
DOI: 10.1063/1.2838312
|View full text |Cite
|
Sign up to set email alerts
|

Compositional investigation of liquid crystal alignment on tantalum oxide via ion beam irradiation

Abstract: The homogeneously aligned liquid crystal display on Ta2O5 via ion beam (IB) irradiation was first embodied with controllability of pretilt angle depending on incident angle of the IB. As a result of x-ray photoelectron spectroscopic analysis, the intensity of Ta–O and O–Ta bondings as a function of incident angle behaved reversely with the pretilt angle and the lowest amplitude was observed at 45°. It revealed that the creation of pretilt angle was attributed to the irradiation of the IB by breaking Ta–O and O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…6 The measurement of the pretilt angle not only showed the tilt angle of the LC molecules against the SnO 2 surface but also indicated that a uniform LC orientation was achieved. The measured TBA 107 transmittance curves of each antiparallel LC cell with IB-irradiated SnO 2 lms are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6 The measurement of the pretilt angle not only showed the tilt angle of the LC molecules against the SnO 2 surface but also indicated that a uniform LC orientation was achieved. The measured TBA 107 transmittance curves of each antiparallel LC cell with IB-irradiated SnO 2 lms are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, serious problems associated with physically contacting the alignment layers have been observed. These include the accumulation of electrostatic charge and generation of fine dust, which destroy thin-film transistors and degrade LCD quality [8]. For these reasons, alternative methods of LC alignment based on non-contact processes have been investigated in an attempt to resolve the shortcomings of the rubbing method.…”
Section: Introductionmentioning
confidence: 99%
“…Strontium oxide is a representative high-k material with a dielectric constant of 13.1 [32] because of which it is a strong alternative candidate for advanced LC applications. Other potential candidates include various inorganic materials with high-k properties, such as Ta 2 O 5 [8], Al 2 O 3 [33], and SnO 2 [34], which have been intensively investigated for their ability to provide enhanced electro-optical (EO) characteristics in LCDs (compared with LCDs fabricated with rubbed PI layers). This indicates that using SrO for the fabrication of LCDs would likely yield LCDs with good EO characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…However, LC alignment is still based on the rubbing of polyimide (PI). The traditional rubbing process for LC alignment has major limitations such as debris and electrostatic discharge, which produce local defects and streaks and result in the degradation of the display resolution [1][2][3][4][5][6]. Over the past several years, there have been a number of challenges to replace PI based rubbing process by nonrubbing methods from methods from traditional oblique deposition, the UV exposure to up-to-data u rubbing, the nanoimprint lithography, and the nanostructured alignment method, which provides controllabililty, nonstop process, and high resolution display, has been intensively investigated with inorganic materials so far.…”
Section: Introductionmentioning
confidence: 99%